2014
DOI: 10.1016/j.brainres.2014.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Programmed hyperphagia secondary to increased hypothalamic SIRT1

Abstract: Small for gestational age (SGA) offspring exhibit reduced hypothalamic neural satiety pathways leading to programmed hyperphagia and adult obesity. Appetite regulatory site, the hypothalamic arcuate nucleus (ARC) contains appetite (NPY/AgRP) and satiety (POMC) neurons. Using in vitro culture of hypothalamic neuroprogenitor cells (NPC) which form the ARC, we demonstrated that SGA offspring exhibit reduced NPC proliferation and neuronal differentiation. bHLH protein Hes1 promotes NPC self-renewal and inhibits di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
6
1
Order By: Relevance
“…Using hypothalamic NPC from newborn rat, we have previously confirmed direct impact of SIRT1 on NPC proliferation and differentiation by both SIRT1 siRNA and exposure to SIRT1 pharmacologic inhibitor and activator. 15 In the present study, despite evidence of maternal overnutrition during fetal life, one day old HF newborns demonstrated normal hypothalamic SIRT1 expression. Nutrition influences on SIRT1 expression remains conflicting, with studies demonstrating that fasting both decreases and increases hypothalamic SIRT1.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…Using hypothalamic NPC from newborn rat, we have previously confirmed direct impact of SIRT1 on NPC proliferation and differentiation by both SIRT1 siRNA and exposure to SIRT1 pharmacologic inhibitor and activator. 15 In the present study, despite evidence of maternal overnutrition during fetal life, one day old HF newborns demonstrated normal hypothalamic SIRT1 expression. Nutrition influences on SIRT1 expression remains conflicting, with studies demonstrating that fasting both decreases and increases hypothalamic SIRT1.…”
Section: Discussioncontrasting
confidence: 39%
“…14 Low birth weight offspring have altered energy sensing, specifically SIRT1 within the hypothalamic arcuate nucleus (ARC), a putative site of appetite regulation. 15 Our studies utilizing both in vivo models and fetal/newborn neuroprogenitor cell (NPC) culture, have indicated that these altered energy sensors effect neurogenic factors which reduce NPC proliferation, induce premature NPC differentiation, and ultimately result in an increase of hypothalamic eating-stimulatory (NPY; neuropeptide Y and AgRP; agouti-related protein) versus eating-inhibitory (POMC; pro-opiomelanocortin) neurons and peptide expression. 15;16;41 …”
Section: Introductionmentioning
confidence: 99%
“…In rodent studies, female offspring exposed prenatally to DDT followed by a high fat diet for 12 weeks in adulthood developed glucose intolerance, hyperinsulinemia, dyslipidemia and altered bile acid metabolism as well as reduced energy expenditure and impaired thermogenesis [389]. DDT effects were also transmitted across generations resulting in obesity in the F3 generation [608]. …”
Section: Mdcs and Metabolism-relevant Diseasesmentioning
confidence: 99%
“…Imprinting, altered DNA methylation, histone modifications and copy number variants have all been implicated in transgenerational phenotype transmission as a result of exposure to chemicals or altered nutrition [610] [615-617]. Candidate sperm epimutations were also identified that could be involved in the etiology of the transgenerational obesity and other disease outcomes [618]. …”
Section: Mdcs and Metabolism-relevant Diseasesmentioning
confidence: 99%
“…Animal studies have demonstrated that perinatal undernutrition may lead to a programmed hyperphagia that in the long term led to adult obesity (5). Previous studies in our laboratory demonstrated that low-protein (LP) rats eat more of a regular chow diet from weaning to 2-month old (6, 7).…”
Section: Introductionmentioning
confidence: 99%